Sobre la traducción y edición de literatura griega moderna y contemporánea en España (1993-2005) - Fernández-González, Vicente; García-Ramírez, Leandro (Universidad de Málaga, 2007)
In order to study the development of the Spanish reception of Modern and Contemporary Greek literature in the second half of the twentieth century and approach more fully the present-day state of the question, it is necessary to avoid a consideration of these five decades as if they constituted a homogeneous period. For the objectives of our study it is posible to distinguish three phases. The first covers the period from the first Spanish editions of the work of Casantsakis (1959) and the poetry of C.P. Cavafis (1962) to the death of the dictator and the beginning of the Spanish transition to democracy (1975). The second one covers the years from 1976 (first publication of Cavafy’s 154 canon poems a few months after Franco´s death) to 1992, an emblematic year in the recent history of Spain. The third phase goes from 1993 to 2005, year in which Liber, the International Book Fair in Madrid, was dedicated to Greece.
Keywords: Literatura griega moderna; Modern and Contemporary Greek literature; Book publishing in Spain; First editions; New editions and reprintings; Literary genres; Retranslation